Североафриканский фронтир: беджа и их соседи = Severoafrikanskiy frontir: bedzha i ikh sosedi - ПИЛИПЧУК , Ярослав (Historia i Świat, 2019)
This paper deals with to the history of relations between the Bija with their neighbors. Bija were subjects of Ancient Egypt and Meroe. They are integrated into these societies without any problems and have been a vassal tribe of them. Beja were restless neighbors of the Roman Empire. They raided Upper Egypt during the III-V centuries AC. Attempts to establish a relationship with them like with the Berbers were unsuccessful. Particularly violent conflicts were a Bija with Christian states – Byzantium Empire, Nubia and Aksum. Some time Bija paid tribute to the Nubians and Axumites. Christianity did not get spread among them, Islam was adopted syncretic form after several centuries of contact with the Arabs. Islamization has been made possible thanks to the settlement of Arabs in the land Bija and participation in the Intercontinental trade. For all their neighbors were threatening nomadic Bija, which made raids to capture people in captivity and selling them into slavery. Bija attacked the Egyptian dominions of the Arab Caliphate, despite the fact that they were formally paid tribute to Arabs.